Association between self-reported bruxism and the academic performance in students of a Private University of Lima – Peru - Huañec Huañec Paucar, Cynthia Lila (2021)
Objective: Evaluate the association between self-reported bruxism and academic performance in students at a university in Lima, Peru. Materials and methods: A total of 203 students were evaluated in this study, between the ages of 19 to 35. Self-reported bruxism was measured using the 'Bruxism Assessment Questionnaire'. Likewise, academic performance was evaluated using the Approval Index Scale. In addition, other variables were included such as employment status, socioeconomic level, stress, anxiety, among others. The association of variables were factored in using the chi-square test and the logistic regression presented the unadjusted and adjusted analisis. Results: The frequency of self-reported awake bruxism and sleep bruxism was 53.20% and 36.45%, respectively. Evidence revealed there was a statistically significant association between awake bruxism with stress and anxiety, and sleep bruxism with anxiety. Students with high academic performance (OR=2.36; IC del 95%:1.06-5.23) and low academic performance (OR=5.72; IC del 95%:1.28-25.57) were found to be more likely to have awake bruxism than those with medium academic performance. Conclusions: This study revealed a statistically significant association between self-reported awake bruxism and academic performance. However, in the future it is suggested to carry out a study with focus only on students with bruxism and with a larger sample of participants with low academic performance to confirm the association found between these variables.